1987
DOI: 10.1037/0278-6133.6.5.431
|View full text |Cite
|
Sign up to set email alerts
|

Parental history of hypertension and screening attendance: Effects of wellness appeal versus threat appeal.

Abstract: This study examined whether the orientation of a health appeal differentially influences health beliefs and early-detection practices among young individuals who are potentially at risk. Undergraduates with and without a hypertensive parent were given printed material about hypertension and the importance of early detection framed in either a wellness or illness-threat format. The major dependent measure was attendance at a blood pressure screening during the week following the experimental session. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…For participants with low-vulnerability beliefs, the reassuring message did not affect intentions to exercise or exercise frequencies. This finding is consistent with previous research (Gintner et al, 1987) and the self-regulatory hypothesis that a reassuring message lacks relevance for individuals who do not have a stable representation of disease risk. While the threat message did not increase their exercise intentions as expected, it did effectively increase their exercise rates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For participants with low-vulnerability beliefs, the reassuring message did not affect intentions to exercise or exercise frequencies. This finding is consistent with previous research (Gintner et al, 1987) and the self-regulatory hypothesis that a reassuring message lacks relevance for individuals who do not have a stable representation of disease risk. While the threat message did not increase their exercise intentions as expected, it did effectively increase their exercise rates.…”
Section: Discussionsupporting
confidence: 92%
“…Empirical findings support the hypotheses that reassuring messages induce immediate and prolonged protection motivation for individuals with beliefs of high disease vulnerability, while threat messages are more effective for those with low-vulnerability beliefs. In a study by Gintner, Rectanus, Achord, and Parker (1987), undergraduates reporting a family history of hypertension (and who presumably perceived themselves as vulnerable to the disease) were more likely than low-vulnerability participants to attend a blood-pressure screening after receiving a wellness message about maintaining healthy blood-pressure levels through frequent monitoring. In contrast, they were less likely than low-vulnerability participants to register for the screening after receiving a threat message stressing the severe consequences of hypertension, Although the self-regulatory model predicts that high-vulnerability participants exposed to the threat message would have increased attendance rates once their fears had subsided, only participants who indicated interest in attending the screening immediately after the message were contacted for scheduling.…”
Section: Vulnerability Beliefs and Health Behavior 1861mentioning
confidence: 99%
“…As a result, the findings of the study may be biased and it may not be appropriate to generalise the findings and conclusions to the general public as a whole. Although laboratory studies looking at the implications of health information and psychosocial factors on behavioural perceptions [28,29] are based on the principal that information processing effects will be similar across socio-demographic groups [15], the stability of the findings of this experiment should be checked in the future with a new sample of respondents, preferably a sample of the general public.…”
Section: Discussionmentioning
confidence: 98%
“…Breast cancer screening has thus far been the most frequently examined detection behavior in this field. While fewer studies have confirmed the original Rothman and Salovey (1997) prediction of loss-framed messages outperforming gain-framed ones when it comes to detection behaviors (in Table 3b, Banks et al, 1995;Williams et al, 2001;Lauver and Rubin, 1990;Myers et al, 1991), most studies failed to find support (Consedine et al, 2007;Finney and Iannotti, 2002;Lalor and Hailey, 1990;Lerman et al, 1992;Park et al, 2010) or even found, if anything, greater support for a gain frame (Apanovitch et al, 2003;Gintner et al, 1987). As an example, Finney and Iannotti (2002) explored an intervention aimed at increasing women's adherence to recommendations for annual mammography screening.…”
Section: Test 3: Considering Empirical Evidence On Health Message Framentioning
confidence: 94%
“…No such framing effects for women with lower levels of perceived susceptibility. Gintner et al, 1987 Loss-framed brochures led to significantly greater change in a positive direction than did gain-framed brochures, which were more effective than were neutral (no frame) brochures…”
Section: Bannon and Schwartz 2006mentioning
confidence: 99%